The Influence of Service Quality and Brand Image Towards Customer Satisfaction in Garuda Indonesia Airlines - syafina dhiaz fhahira; ra afera ratna wijayanti; muhammad affandi; joni gusmali (IULI Publisher, 2023)
When consumers buy a product, there are many factors that influence these consumers in making decisions, starting from internal factors or external factors to produce satisfaction for the consumers themselves. Service quality is one aspect when consumers use services or buy products from a trademark or company. Service quality is the main activity carried out by a trademark or company to provide satisfactory service to consumers in the long run. The aviation business is one of the industries that is concerned with the quality of their service to provide the best service to consumers so that consumers are satisfied with the services provided. In addition to service quality, brand image is also an important aspect of customer satisfaction because consumers will see whether a trademark or company has a good image or not and consumers will use services or goods from brands or companies that they frequently use or that already exist in their minds. The purpose of this study is to analyze the impact of service quality and brand image on customer satisfaction in the aviation industry. This study uses descriptive and quantitative research with the aim of wanting to know the relationship of three variables namely service quality, brand image and customer satisfaction with each sub-variable. This study uses quantitative data by distributing questionnaires as a method of collecting data. Keywords: Service Quality, Brand Image, Customer Satisfaction, Airline Industry